PERBANYAKAN AMORPHOPHALLUS TITANUM BECC (ARACEAE) DENGAN TEKNOLOGI IN VITRO - ,, Witjaksono; Nugraheni, Katarina Utami; Hoesen, Djadja SH; ,, Irawati (JURNAL BIOLOGI INDONESIA, 2012)
Propagation of Amorphophallus titanum Becc (Araceae) via In Vitro Technology. Amorphophallus titanum is a unique plant with gigantic inflorescence and radiating corpselike odorl and therefore has become a botanical flagship and attract visitors. Its existence innature may be endangered due to habitat conversion that reduce population size required for cross pollination to occur. Propagation via non-conventional technique is much needed for the resulting planting material to be exchanged among botanical garden or even traders. Mass propagation using in vitro technology has been successful. An improvement of the propagation method has been developed by incorporating high level of cyitokinin BA of 1-2 mg/l in the medium for shoot proliferation and lowering it to 0-0,1 mg/l for shoot elongation. Shoot elongation is effectively influenced by age and the phase of medium whereas the liquid phase induced the enlargement of the shoots significantly without even promoting any hyperhidricity.The plantlets produced survive acclimatization.Key words: Amorphophallus titanum, mass propagation, in vitro, mediurm cair, BA.